2020
DOI: 10.4102/ajlm.v9i1.812
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary schistosomiasis amongst primary school children in Ikwo and Ohaukwu Communities of Ebonyi State, Nigeria

Abstract: Background:Urinary schistosomiasis is a serious public health challenge in some communities of Ebonyi State, south-east Nigeria, partly resulting from a lack of adequate epidemiological data for the institution of effective control strategies.Objective: This study evaluated the prevalence and risk factors of urinary schistosomiasis in rural communities of Ebonyi State, south-east Nigeria.Methods: A total of 300 students, comprising 185 boys and 115 girls, were randomly selected for the study between July and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 12 publications
11
16
1
Order By: Relevance
“…The result obtained from the study showed the abundance and diversity of freshwater snail intermediate hosts in the water canals studied. This abundance and diversity of freshwater snail hosts are of public health importance because of the eminent risks to human infections his finding corroborates with that of [1,18] that the presence of freshwater snails is of public health importance because of the indication for parasitic transmission.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The result obtained from the study showed the abundance and diversity of freshwater snail intermediate hosts in the water canals studied. This abundance and diversity of freshwater snail hosts are of public health importance because of the eminent risks to human infections his finding corroborates with that of [1,18] that the presence of freshwater snails is of public health importance because of the indication for parasitic transmission.…”
Section: Resultssupporting
confidence: 84%
“…Urinary schistosomias is constitutes a major infection of public health importance in Nigeria and affects mainly the rural poor and some disadvantaged urban populations [14][15][16]. It is characterized by haematuria, dysuria, bladder wall pathology, hydronephrosis (swelling of kidney due to build-up of urine), It can also present with squamous cell carcinoma [14,17,18]. In adults, the infection…”
mentioning
confidence: 99%
“…This abundance and diversity of freshwater snail hosts are of public health importance because of the increased risks to human infections. This finding corroborates with that of [1,18] which argued that because of the increased presence of freshwater snails during the dry season, that public health professionals should, as of optimal importance, health educate residents living near water canals on the need to reduce regular contacts with freshwater canals during dry season. This is to minimize the parasitic transmission of diseases including schistosomiasis.…”
Section: Discussionsupporting
confidence: 86%
“…Urinary schistosomiasis constitutes a major infection of public health importance in Nigeria and affects mainly the rural poor and disadvantaged urban populations [14][15][16]. It is characterized by haematuria, dysuria, bladder wall pathology, hydronephrosis (swelling of kidney due to build-up of urine), and can also present with squamous cell carcinoma [17][18][19]. In adults, the infection can result to genital ulcers and other types of lesions that can cause poor reproductive health with sexual dysfunction and infertility.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of UgS in Nigeria varies from region to region, with some areas having much higher prevalence [21,22,23,24] than others [10,25,26,27].…”
Section: Epidemiological Status In Nigeriamentioning
confidence: 99%